(untitled) (Journal of Pharmaceutical Negative Results, 2022)
The purpose of the study was to assess the relationship between Success Materialism and Happiness Materialism and show how these two dimensions of materialism influence an individual’s life satisfaction. The sample consisted of 80 males in the age range of 40-50 years with annual income of 8-10 lakhs INR. The tools used in the study were Satisfaction with Life Scale by Diener, Emmons, Larsen, and Griffin and Material Value Scale by Richins and Dawson. The results were analyzed using statistical tools for correlation and regression. The results indicated that happiness materialism has a significantly negative correlation with life satisfaction(r=-0.339,p<0.01). Success materialism and happiness materialism together contribute 9.4% variance in predicting life satisfaction, found to be significant at 0.01 level. The study concluded that happiness materialism can lead a person to be dissatisfied with their current standard of living and other pleasures of life which in turn negatively influence overall life satisfaction.